2023
DOI: 10.31004/joe.v5i2.867
|View full text |Cite
|
Sign up to set email alerts
|

Meningkatkan Profesional Guru dengan Program Pendidikan Profesi Guru (PPG)

Abstract: The development of professional teachers is protected by the Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers and Government Regulation of the Republic of Indonesia Number 74 of 2008 concerning Teacher Certification. Educator certification for teachers is obtained through professional education programs organized by tertiary institutions that have programs for procuring accredited education staff, both those held by the government and the community, which are then determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Guru yang dapat menunjukkan kemampuannya saat mengajar dapat dianggap sebagai guru professional (Hanun, 2021). Guru professional tidak hanya diharapkan memiliki penguasaan akademik dan keterampilan di bidang studinya, tetapi juga mampu melaksanakan seluruh tahapan kegiatan dalam proses pembelajaran (Maulana et al, 2023). Guru profesional diharapkan dapat mengelola semua langkah kegiatan dalam proses pembelajaran dengan baik untuk mencapai hasil pembelajaran yang optimal (Abdillah et al, 2021).…”
Section: Pendahuluanunclassified
“…Guru yang dapat menunjukkan kemampuannya saat mengajar dapat dianggap sebagai guru professional (Hanun, 2021). Guru professional tidak hanya diharapkan memiliki penguasaan akademik dan keterampilan di bidang studinya, tetapi juga mampu melaksanakan seluruh tahapan kegiatan dalam proses pembelajaran (Maulana et al, 2023). Guru profesional diharapkan dapat mengelola semua langkah kegiatan dalam proses pembelajaran dengan baik untuk mencapai hasil pembelajaran yang optimal (Abdillah et al, 2021).…”
Section: Pendahuluanunclassified
“…Moses Adeleke Adeoye / Impact of School-University Partnerships and Professional Learning Communities Professional learning communities have also been shown to lead to improved teaching practices, increased collaboration among teachers, and improved student learning outcomes. The National Center for Education Evaluation and Regional Assistance found that teachers who participated in professional learning communities reported improved teaching practices and increased collaboration with their colleagues (DeMonte & Hanna, 2014;Maulana et al, 2023). Another study by the University of Minnesota found that professional learning communities led to improved student learning outcomes, increased teacher satisfaction and improved social-emotional learning for students (Vescio et al, 2008).…”
Section: The Challenges and Limitations Of Professional Learning Comm...mentioning
confidence: 99%
“…Not everyone is capable of becoming a teacher. Teaching is a profession because not everyone can be educated in the field (Galih & Iriani, 2018;Maulana et al, 2023). Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers states that teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in formal early childhood education, basic education, and secondary education.…”
Section: Introductionmentioning
confidence: 99%
“…The government has made various efforts to actualize teachers' professional competence. One program that supports teacher professional development is the Teacher Professional Education program (Hanun, 2021;Maulana et al, 2023). Through Teacher Professional Education activities, it is hoped that teachers will be able to increase understanding regarding HOTS because, in Teacher Professional Education activities, teachers are given an understanding of the concept of HOTS, applying HOTS to the learning process, and preparing HOTS questions (Harjanti et al, 2022;Poerwanti & Tribudhiarto, 2020).…”
Section: Introductionmentioning
confidence: 99%